Diel factors of wolf and moose kill rates - Vander Vennen, Lucas M.; Patterson, Brent R.; Rodgers, Arthur R.; Moffatt, Scott; Anderson, Morgan L.; Fryxell, John M. (Dryad Digital Repository, 2016)
Wolf and moose movement rate data collected from GPS collared animals in northern Ontario, and represent population-level average movement rate during each of the 16 time bins throughout the 24-hour cycle. Kill rate is the distribution throughout the 16 time bins of the time of kill from field-verified sites of wolves predating on moose. Crepuscular light conditions were calculated as the average proportion of a twilight period within each time bin, and total light conditions were calculated from a crude model assuming 0 for night, 0.5 for twilight, and 1 for daylight.